Silicone Rubber Material Innovation and Application: The Key to Industrial Upgrading - Min Yang (Innovation in Science and Technology, 2025)
This paper delves into how the innovation of silicone rubber materials has become a crucial force in driving the upgrading of the silicone rubber production and processing industry. With the rapid development of modern industry, higher requirements for the performance and functionality of silicone rubber materials have emerged. The paper first analyzes the current status of silicone rubber materials and their limitations in traditional application fields, pointing out the challenges faced by current industrial upgrading, such as increasingly strict environmental protection requirements, increased demand for high performance, and intensified international competition. Next, the paper explores the innovation trends of silicone rubber materials, including high performance, environmental friendliness, multifunctionality, and the application of new processing technologies (such as nanotechnology and 3D printing technology). These innovations not only enhance the performance of silicone rubber materials but also expand their application fields, enabling them to meet the needs of high-end industries such as aerospace, electronics, medical, and automotive.